Precise Engineering and Efficient Biosynthesis of Robust and High‐Activity Human Haemoglobin for Artificial Oxygen Carriers - Fan Liu; Jingwen Zhou; Jianghua Li; Jian Chen; Guocheng Du; Xinrui Zhao (Microbial Biotechnology)
ABSTRACT Recombinant human haemoglobin (rHb) is a tetramer protein with heme as cofactors, which have extensive applications in the fields of biomaterials and biomedical therapeutics. However, due to the poor structural stability, the dissociation of heme, weak oxygen transport efficiency, and lower activity, the utilisation of rHb is severely limited in artificial oxygen carriers. Herein, based on the novel developed high‐throughput screening strategies and semi‐rational design, the engineered rHb mutant with strong stability and heme‐binding ability was obtained. In addition, through the homology alignment and rational design, the oxygen transport capacity of rHb was significantly enhanced. Furthermore, the bottlenecks of heme supply were overcome by applying the fine‐tuned heme synthesis in Escherichia coli. Finally, the robust and high‐activity rHb mutant was synthesised and can be used as a new generation of artificial oxygen carriers.